THE CHANGE OF POSITION DEFENCE IN MALAYSIAN UNJUST(IFIED) ENRICHMENT: REFLECTIONS FROM ENGLISH LAW - CHOI, JOHN (CHING JACK) (Journal of Malaysian and Comparative Law, 2025)
In England and in Malaysia, the recognition of unjust or unjustified enrichment has necessitated the simultaneous acceptance of a defence of change of position. In stark contrast with the English experience, the leading apex-court decision in Malaysia, which recognised this new private law action, made no elaboration on the defence. This article hopes to fill that gap by evaluating the normative place of change of position against four peculiarities of the Malaysian unjust(ified)-enrichment-and-restitution landscape. The first feature is the existence of a statutory restitutionary regime provided for by the Contracts Act 1950, which stands in parallel with this newly recognised liability at common law. The second feature is the seemingly adopted ‘value surviving’ test for enrichment, as opposed to a ‘value received’ model. The third feature is Malaysian law’s adoption of the Civilian-inspired ‘absence of basis’ approach. The fourth feature is the elusive ‘unconscionability’ inquiry that has crept into the unjust(ified) enrichment framework. Each of these features interacts with the change of position defence in a manner which presents unique and unresolved challenges to the doctrinal coherence of this still-nascent legal subject.